Tönnies' concept of public opinion and its utility for the academic field - Arnold, Anne-Katrin (Javnost (Ljubljana), 2007)
This paper approaches the building of an integrative conceptual model of the study of public opinion and popular sentiments by applying the theory of public opinion developed by Ferdinand Tönnies to the general field of public opinion research and theory. Tönnies' theoretical foundations are systematised and extended to suggest a framework that could be useful for integrating the field and improving consistency as well as efficiency of opinion research. The cornerstones of this model are two forms of social will:popular sentiment and opinion of the public. The paper discusses the derivation of these dimensions, their specification, and several features.
Keywords: Tönnies, Ferdinand; javnost; javno mnenje